1998
DOI: 10.1111/j.1471-0528.1998.tb09351.x
|View full text |Cite
|
Sign up to set email alerts
|

First trimester sonographic detection of chromosomal abnormalities in an unselected population

Abstract: Objective To investigate the role of first trimester sonography in detecting chromosomal abnormalities in an unselected obstetric population. Conclusions A significant proportion of fetal chromosomal abnormalities can be detected by first trimester sonographic screening to assess fetal structural appearance. The sensitivity of detection can be improved by combining measurement of nuchal translucency with detailed examination of fetal anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 24 publications
(26 reference statements)
2
34
0
2
Order By: Relevance
“…Present research focuses on finding markers which will increase the effectiveness of prenatal screening while restricting the number of fetal sampling procedures. Serum assays [2][3][4][5][6], heart rate [7] and early fetal morphology [8] are screening techniques currently undergoing evaluation. Fetal nuchal translucency (NT) thickness seems to be a marker which has been validated in both high-and low-risk populations [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Present research focuses on finding markers which will increase the effectiveness of prenatal screening while restricting the number of fetal sampling procedures. Serum assays [2][3][4][5][6], heart rate [7] and early fetal morphology [8] are screening techniques currently undergoing evaluation. Fetal nuchal translucency (NT) thickness seems to be a marker which has been validated in both high-and low-risk populations [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Among 23 cases of trisomy 21, 9.0% (n = 2) had structural abnormalities. Similarly, Economides et al 5 found a structural abnormality in 1 of 8 cases of trisomy 21 in the first trimester. In comparison, in a series of 46 cases of trisomy 13, holoprosencephaly was diagnosed in 24%, and omphalocele was diagnosed in 10%.…”
Section: Major or Structural Abnormalities And Fetal Aneuploidymentioning
confidence: 99%
“…[49][50][51][52][53][54][55][56] However, as outlined above, NT increases with gestational age, and the degree of risk has been found to vary with NT measurements. 5,57 Therefore, it was natural to express NT measurements relative to gestational age or crown-rump length as a delta value or multiple of the median (MoM). Multiple of the median data and derived likelihood ratios can then be used to estimate the patient-specific risk.…”
Section: Technique and Measurementmentioning
confidence: 99%
“…The findings of many studies suggest that effective first trimester screening for trisomy 21 can be provided only by the combination of maternal age and measurement of fetal NT (Pajkrt E et al, 1998;Economides DL et al, 1998;Bindra R et al, 2002;Liu SS et al, 2004;Rozenberg P et al, 2006;Westin M et al, 2006;Czuba B et al, 2007;Kagan KO et al, 2010). At a risk cut-off of 1 in 100, the detection rate of trisomy 21 is about 75%, at a false positive rate of about 2%.…”
Section: Detection Ratementioning
confidence: 99%